Romantic Name for a Deadly Condition: Kissing Aneurysms of the Pericallosal Artery – A Case Report - M. Waszak, Przemyslaw; Paturej, Agnieszka; Springer, Janusz; Baranowska, Katarzyna; Brzeska, Barbara; Aleksandrowicz, Katarzyna; Szmuda, Tomasz; Garnier, Hanna (International Journal of Medical Students, 2015)
Background: Kissing aneurysms are two independent but adjacent aneurysms protruding from two contralateral arterial locations. This report describes a successfully treated case of kissing aneurysms at the Department of Neurosurgery, Medical University of Gdansk. Case: A 45-year-old asymptomatic woman was diagnosed with unruptured bilateral aneurysms located in the pericallosal-callosomarginal division. Her medical history included a previous intracranial aneurysm and arterial hypertension. The patient underwent a successful treatment by surgical clipping and was discharged in good condition; neither disability nor neurologic deficit was noticed upon discharge. Surgical wound healing was complicated by an infection and resulted in a reoperation for the patient. Conclusion: The etiology of kissing aneurysms is still unknown and the best treatment method stills remains unclear. Thus, every case has to be carefully and individually assessed by an interdisciplinaryteam. As a result, patient transfer to an experienced neurosurgical center could be beneficial.